DICHOTOMOUS KEYS: BASIC TOOLS FOR BIOLOGICAL IDENTIFICATION - Burelo Ramos, Carlos Manuel; Cid Martínez, Marcela Alejandra (Kuxulkab', 2022)
A dichotomous key is a logically organized sequence, in which opposing (dual) and exclusive characteristics are exposed through the use of morphological characters (micro and macro morphological, morphometric measurements and meristic characters) and their state; whose usefulness is the accurate identification of a specific species or taxon that is intended to be rapid. In this work the basic characteristics for its elaboration and use are exposed, such as the use of a simple technical vocabulary, the use of gerunds and participles, among others.
Keywords: Morphological characters; Name taxa; Systematic; Biodiversity